Global market opportunities for SMEs: Export/import perception and trade growth in Lesotho - Oluwafemi O. Ojo; Ojo J. Adelakun (The Southern African Journal of Entrepreneurship and Small Business Management)
Background: Given the economic situation of Lesotho, where small and medium-sized enterprises (SMEs) are key drivers of employment and growth, it is critical to understand the factors impacting their foreign trade operations.